Charging method and system - JUNXIAN MO (2007)
The method can be used in the access technique in the wireless MAN. The method includes these steps: after the data channel/ business flow was built, the charging point (CP) sends the request of data-channel/ business-flow start charging to the charging server; after the business flow/ data channel was shut, CP sends the request of Business-flow/ Data-channel ending charging; according to these two requests, the charging server charges. The invention also discloses a charging system, a charging point and a charging server as well. Via this invention, the charges on the basis of the data channel and on the business flow are realized. The invention provides a more reasonable, more precision charging method for the telecom vender. Thus the user satisfactory and the network resource utilization are raised.